Consequences and Coping Strategies Among Students and Workers Experiencing Stalking - Daniela Acquadro Maran; Antonella Varetto; Tatiana Begotti; Amelia Rizzo; Murat Yıldırım; Kavita Batra; Hicham Khabbache; Francesco Chirico (Iranian Rehabilitation Journal, 2025)
Objectives: This study aimed to compare the experience of stalking victimization among students and workers, considering the prevalence of the phenomenon, physical and emotional consequences, and coping strategies Methods: A total of 291 students (51.9%) and 270 workers (48.1%) who were victims of stalking completed an anonymous questionnaire. Results: The results showed that the reported behaviors were consistent with a higher percentage of workers experiencing mediated and interactive contact, harassment, and physical violence. Students also reported more physical and emotional symptoms than workers, with some significant differences (loss/increase of appetite, nausea, self-inflicted injuries, panic attacks, suicidal thoughts, sadness, confusion, lack of trust in others, aggressiveness, paranoia, irritability, and agoraphobia). Moreover, interactive contact was associated with physical and emotional symptoms in students, while in workers, the same behavior was only associated with emotional symptoms. Regarding coping strategies, results showed that students were more likely to report increased social contact. Discussion: This research can guide intervention and prevention strategies, such as promoting educational campaigns for bystanders rather than only for victims.